The coalition of three f: family, friend and firms; a study on migrant entrepreneurs in Mumbai - Talukdar, Bedanga; Roy, Archana K. (International Journal Of Community Medicine And Public Health, 2022)
Background: The paper examines how family and friends help successfully manage a firm and support in entrepreneurial activities. Entrepreneurial activity necessitates long-enduring working hours and often involves financial and emotional hardships. The study explores the collective effect of migrants’ social capital, i.e., family and friend which facilitating labour and finance at new location. Methods: For the present study, the primary survey was conducted in Mumbai from February 2018 to August 2018. A total sample of 540 self-employed migrants operating the business in Mumbai were interviewed. Results: There are distinctive migration network channels in the form of family relatives, kin, friends, co-villager, local acquaintance. Age and marital status have surfaced to be paramount predictors for choosing self-employment. Confounders like bonds among family members, kins, friends and community support play an important in operating the enterprise. Results from logistic regression suggest that married entrepreneurs are 0.64 times more likely to have higher income than the never married individuals. Firms where spouses were actively engaged, were more likely to have higher income than reference category. The number of family members living together and helping firm activity is statistically significant with better business performance. Concussions: Salient findings suggest there is a greater degree of reliance among household members in migrant families. Migrant family members depict interpersonal bonds and common self-interest to provide financial and labour resource that helps in establishing and operating a business. Migrant network plays a key role in facilitating informal lending institutions providing credit and finance.